EFEKTIVITAS PROGRAM TEMPAT PENGOLAHAN SAMPAH REUSE REDUCE RECYCLE KUPAS DALAM PENGELOLAAN SAMPAH DI KALURAHAN PANGGUNGHARJO KAPANEWON SEWON KABUPATEN BANTUL - Laia, Nurlinda; Utami, Sri (PARADIGMA: Jurnal Ilmu Administrasi, 2025)
Household waste management in Indonesia remains a crucial issue involving the government, communities, and non-governmental organizations. Waste is a residual material discarded due to its perceived lack of value. Improper management can negatively impact the environment, health, and public safety, leading to pollution. According to the Regulation of the Minister of Public Works No. 3 of 2013 on Household Waste Management Infrastructure and Facilities, waste handling involves sorting at the source based on the 3R principles (Reduce, Reuse, Recycle), collection, processing, residue transport, and final disposal. This study was conducted in Panggungharjo Village, Sewon Sub-district, Bantul Regency, to examine the effectiveness of the TPS3R KUPAS program in waste management and identify its supporting and inhibiting factors. The effectiveness indicators used include program understanding, target accuracy, timeliness, goal achievement, and tangible change. This qualitative descriptive research employed observation, interviews, and documentation as data collection techniques. Informants were selected using purposive and snowball sampling, while data were analyzed through the stages of collection, reduction, presentation, and conclusion drawing. The findings indicate that the effectiveness of the TPS3R KUPAS program is moderate. The indicators of program understanding, target accuracy, and tangible change show low achievement. The timeliness indicator is fulfilled since waste collection and processing generally follow the schedule, although occasionally hindered by technical problems. The goal achievement indicator is partially met, evidenced by the program’s contribution to reducing waste volume at the landfill, though its impact declined after the discontinuation of the incinerator. Supporting factors include trained human resources, stakeholder collaboration, adequate facilities, marketing networks, and economic benefits. In contrast, inhibiting factors involve low public participation, limited equipment, lack of continuous socialization, odor issues, weak supervision, and low maintenance awareness among workers.